Characterizations on The Effect of Iron (III) Nitrate Catalyst on the Synthesis of Reduced Graphene Oxide from Bamboo Derived Graphite - N.A Karim; Muhammad M. Ramli; Ismariza Ismail; Shazlina Johari; C.M.R Ghazali; Retno Asih (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
Bamboo-derived graphite was used to make reduced graphene oxide (rGO) from pyrolysis with Iron (III) Nitrate acting as a catalyst for significant success in producing rGO from bamboo in a sustainable and renewable manner. Bamboo grown in Peru, Malaysia (Gigantochloa albociliata) was chosen. The process of producing bamboo charcoal involved pyrolysis at 800°C under an inert nitrogen atmosphere, with a heating rate of 10°C per minute and a soaking time of 3 hours. Bamboo charcoal that was prepared was activated using Iron (III) Nitrate at four different concentrations of the catalyst (0 %, 10 %, 20 % and 30 %) before exfoliation to and reduction to rGO. Characterization of structure and morphology were completed with X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) and Raman Spectroscopy. Results of this study show that activating bamboo charcoal with Iron (III) Nitrate (20 %) made the best rGO in terms of graphitization, surface roughness, and porosity with maintained structural integrity (fine microstructural detail). This study also shows that rGO produced from bamboo charcoal has many uses such as water purification, energy storage, electromagnetic wave absorption and environmental remediation. This work demonstrates that there continues to be a growing need for affordable and environmentally friendly synthetic graphite as bamboo represents a possible and viable renewable alternative to non-renewable carbon sources for the production of advanced nanomaterials.